Exploring Maps at Different Orientations and Effects on Blind Users - Naquiah Abd Hamid, Nazatul; Adilah Wan Adnan, Wan; Hanis Abdul Razak, Fariza (International Journal of Engineering and Technology, 2018)
Maps have been used to facilitate travellers in wayfinding and they are normally read at different orientations. A multimodal map has been introduced to enable blind people to learn maps. However, such maps usually enable them to explore maps in a fixed orientation. The effect of exploring maps in such way on user cognitive maps and sense of directions is unknown. Therefore, this paper investigates the effect on blind peopleâ€™s cognitive maps and their sense of directions. Results showed that in the rotatable condition, some blind people have the ability to build accurate cognitive maps of the tested maps as accurate as in the static condition. Blind people were found able to point to the direction accurately in the rotatable condition than in the static condition. This was supported by their scores when reconstructing maps. However, there were no correlations found between user sense of directions and their pointing accuracy.Â Â